A variação interespecífica no tamanho floral determina a florivoria em uma área úmida tropical sazonalmente inundável - Ortiz Albornoz, Gabriela Liliana (2022)
The effects of floral damage caused by florivores usually involve negative consequences on plant reproduction. However, the factors affecting the plant-florivore interaction are still poorly understood, especially the role of abiotic factors and the variation among multiple species within ecosystems. Thus, it is largely required to determine the patterns of florivory incidence and its consequences for plant communities. Here, we assessed the potential influence of abiotic factors related to climatic seasonality, of phylogenetic relationships among plants, and of functional attributes associated with attractiveness to pollinators on florivory in the Pantanal, a seasonally flooded tropical savanna that encompasses one of the world’s largest wetlands. Between December 2020 and November 2021, the percentage of area removed in petals (or tepals) and the percentage of flowers attacked by florivores were examined in 51 species from 25 families, considering flowering season (dry or rainy), the substrate where the plants occur (aquatic or terrestrial), and floral attributes (flower size, arrangement, and color) as potentially determining factors in the incidence of florivory. Our results showed that phylogeny and environmental factors (season and substrate) did not have a significant influence on florivory. The only determinant of interspecific variation in flower removed area and frequency of attacked flowers was flower size, where larger flowers experienced a higher incidence of florivory regardless of season and substrate, while flower arrangement and color were not significant factors. Our study is one of the first to jointly estimate the effects of biotic and abiotic factors on both the level of floral damage and the frequency of attack by florivores at the community level. The results show that flower size is a crucial attribute in determining plant-florivore interactions, a widespread but still underlooked antagonistic interaction in a seasonally flooded tropical savanna.